Influence of the Radial Inertia Effect on the Propagation Law of Stress Waves in Thin-Walled Tubes (Advances in Applied Mathematics and Mechanics, 2023)
This investigation focused on the influence of the radial inertia effect on thepropagation behavior of stress waves in thin-walled tubes subjected to combined longitudinal and torsional impact loads. Generalized characteristics theory was used toanalyze the main features of the characteristic wave speeds and simple wave solutionsin thin-walled tubes. The incremental elastic-plastic constitutive relations describedby the rate-independent plasticity were adopted, and the finite difference methodwas used to investigate the evolution and propagation behaviors of combined elastic-plastic stress waves in thin-walled tubes when the radial inertial effect was considered.The numerical results were compared with those obtained when the radial inertia effect was not considered. The results showed that the speed of the coupled stress waveincreased when the radial inertia effect was considered. The hardening modulus of thematerial in the plastic stage had a greater impact on the coupled slow waves than onthe coupled fast waves.